Are patients and relatives the better innovators? The case of medical smartphone applications - Moritz Goeldner; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2016)
Prior research has shown that users are a valuable resource for identifying new product or service innovations. However, few scholars have analyzed how different user types such as intermediate and end users are interacting along the value chain of an emerging new product and how they contribute to innovation. Further, user innovation success in the market is often unclear, since very few innovations diffuse directly to customers from the user innovators. We analyze different innovative contributions of intermediate and end users that have been sold and evaluated within the healthcare sector. Several studies in the healthcare sector have shown that healthcare professionals are an important source of innovation. Yet, to date, companies and scholars have paid little attention to the end users of medical devices: patients. We focus on the innovative behavior of patients and their relatives, their motivations, and their contributions to improving the quality of their own and ultimately of other patients' therapy. We analyze innovations of producers, healthcare professionals, patients, and relatives in the German, UK, and U.S. markets for medical smartphone apps (Apple App Store) and conduct 16 semi-structured interviews. Our findings show that users develop around 46% of all medical smartphone applications (apps). We analyzed 510,229 user ratings and found that apps designed by patients, relatives, and healthcare professionals are rated significantly better by App Store customers than apps created by professional software companies. Apps developed by patients' relatives achieve significantly more downloads and generate on average three times higher revenues per year. The initial medical smartphone app developments in the early days of the Apple App Store were mainly triggered by healthcare professionals. The interview data shows the extensive medical knowledge of patients and their relatives, particularly those with chronic diseases. The overall findings are in line with a current literature stream that indicates that patients are gaining more influence on their treatment, are better informed, and are taking more actions to increase their quality of life. Commercial healthcare companies should take advantage of this and should consider including patients and relatives into their product development.
Keywords: 330; user innovation; patient; relative; healthcare professional; m-health; medical; smartphone applications; app; apps